Enhancing Literacy Skills Through Interactive Learning Approaches - Ahmad Ahmad; Nur Rahmo; Dedi Harianto; Sri Asmira; Nurwahida Nurwahida (PT. Global Research Collaboration, 2024)
This study aims to improve students' literacy skills at Sekolah Pustaka Lontara through interactive literacy-based learning. The issue of low reading interest and literacy comprehension among students has prompted the need for more effective and enjoyable teaching methods. The interactive learning implemented includes activities such as group reading, group discussions, and educational games designed to stimulate interest and reading skills. The research uses a qualitative approach with techniques such as observation, interviews, and analysis of students' learning outcomes. The results show a significant improvement in students' literacy comprehension, reflected in literacy test results and student responses to reading activities. The use of interactive learning also encourages students to be more actively engaged and enjoy the learning process. This program demonstrates that an interactive approach can be an effective solution to enhancing literacy skills in schools facing challenges related to resources and student interest. The study recommends integrating interactive methods into the curriculum to achieve more optimal literacy outcomes.